2005
DOI: 10.1016/j.proci.2004.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Flame inhibition by phosphorus-containing compounds in lean and rich propane flames

Abstract: Chemical inhibition of laminar propane flames by organophosphorus compounds has been studied experimentally, using a laboratory Mache Hebra nozzle burner and a flat flame burner with molecular beam mass spectrometry (MBMS), and with a computational flame model using a detailed chemical kinetic reaction mechanism. Both fuel-lean and fuel-rich propane flames were studied to examine the role of equivalence ratio in flame inhibition. The experiments examined a wide variety of organophosphorus compounds. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 30 publications
1
55
0
Order By: Relevance
“…Later, the model was refined by altering the rate constants of six key steps and was successfully applied to calculating the structure of flames at atmospheric pressure. The enthalpies of formation of phosphorus oxyacids were calculated by various quantum-chemical methods (Glaude et al, 2000;Mackie et al, 2002;Korobeinichev et al, 2005). At the same time, the enthalpies of formation of some activated complexes were calculated by varying their structures (intermediate states) for different pathways of the key reactions.…”
Section: Simulation Of the Structure And Speed Of A Laminar Flamementioning
confidence: 99%
“…Later, the model was refined by altering the rate constants of six key steps and was successfully applied to calculating the structure of flames at atmospheric pressure. The enthalpies of formation of phosphorus oxyacids were calculated by various quantum-chemical methods (Glaude et al, 2000;Mackie et al, 2002;Korobeinichev et al, 2005). At the same time, the enthalpies of formation of some activated complexes were calculated by varying their structures (intermediate states) for different pathways of the key reactions.…”
Section: Simulation Of the Structure And Speed Of A Laminar Flamementioning
confidence: 99%
“…The thermochemistry of the reactions involving organophosphorus compounds (OPCs) was studied by Glaude et al [15] using ab initio quantum-chemical calculations for many new substances. The mechanism of the reactions involving OPCs was further developed in [16] and used to explain the inhibition of propane flames.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10-15 years, a number of researchers have shown that the mechanism of flame inhibition by phosphorus-containing compounds involves their influence on the recombination rate of atoms and free radicals in the flame [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The recombination reactions are catalyzed by phosphorus oxides and phosphoric acids.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that none of the models describe the concentration profiles of these compounds adequately. The structure and propagation velocity of atmospheric premixed propane-oxygen and propaneair flames doped with TMP was studied in [11,12]. It was established that a change in the stoichiometric composition of the combustible mixture resulted in a change in the composition of phosphorus-containing products of TMP combustion, which, in turn, changed the inhibition efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation